The relationship of stride length and walking pain to the dynamic balance of the elderly: The relationship of stride length and walking pain to the dynamic balance of the elderly - -, Nabila Tri Lestari; Munawwarah, Muthiah; Meidian, Abdul Chalik; Noviati, Nuraini Diah (Indonesian Journal of Physiotherapy, 2025)
Background: Changes in stride length are something that is closely related to unhealthy conditions and is a decrease in the ability to carry out activities independently. Nearly 50% of people over the age of 65 have problems walking. Method: This is a cross sectional study, the sample consisted of 34 people at Posyandu for the Elderly Melati Putih RW 02 East Jakarta. The sample was measured for stride length using a meterline with units measured in cm and dynamic balance was measured using the TUG test with units of time measured in seconds using a stopwatch. Results: The mean ± SD value for the step length variable was 79.14 ± 12.63, the mean value for the walking pain variable was 4.97 ± 1.62 and the mean value for the dynamic balance variable was 21.18 ± 6.63. Testing normality using the Shapiro Wilk Test, the data obtained a normal distribution of 2 and abnormally 1, while with hypothesis testing using Spearman Rank Correlation, the p value was <0.05 and had a value of r -0.738 for step length on dynamic balance and r 0.617 for walking pain on balance. dynamic, thus showing that Ha is accepted, meaning there is a relationship between step length, walking pain and dynamic balance in the elderly. Conclusion: There is a relationship between stride length, walking pain and dynamic balance in the elderly. Keywords: Stride Length; Dynamic Balance; Pain; Fall Risk